Profesionalisme Tenaga Administrasi Sekolah dalam Pelaksanaan Administrasi Perkantoran di SMP Negeri 3 Padang Panjang - Aprizal Ahmad; Wanda Fitri; Jesi Norisah (Al-Munawwarah : Jurnal Pendidikan Islam, 2021)
This research is motivated by the existence of a regulation of the minister of national education number 24 of 2008, school administrative staff or education personnel are generally required to have three basic competencies, namely personality competence, social competence and technical competence, as well as one additional competency, namely managerial competence that must be possessed by administrative or administrative staff. The purpose of this study was to determine and describe (1) To determine the implementation of administrative personnel at SMP Negeri 3 Padang Panjang. (2) To determine the professionalism of administrative staff at SMP Negeri 3 Padang Panjang. (3) To determine the factors that affect the professionalism of Administrative Personnel at SMP Negeri 3 Padang Panjang. This research uses a qualitative descriptive method. The main data sources in this study were the principal, treasurer of administrative staff, financial administration staff and administration of facilities and infrastructure at SMP Negeri 3 Padang Panjang. Data collection techniques are observation, interview and documentation. Data analysis techniques in research are data reduction, data presentation, and conclusions. The results of this study are: (1) The implementation of administrative staff at SMP Negeri 3 Padang Panjang has tried to improve their scientific insights, as well as trying to improve their quality to support a good and conducive administrative implementation process as desired and what is desired has been achieved. (2) The professionalism of Administrative Personnel at SMP Negeri 3 Padang Panjang can be said to be professional because they already have four competencies, namely personality competence, social competence, technical competence, managerial competence as well as being responsible and trustworthy in carrying out their duties according to the applicable main duties and functions. In principle, it already has four competencies, but for personality competence, especially in the discipline aspect, it is still lacking, this is shown by there are still administrative staff who are late for work. (3) The factors that influence the Professionalism of Administrative Personnel at SMP Negeri 3 Padang Panjang are divided into two factors. Internal factors are divided into two parts. Intrinsic motivation and extrinsic motivation, while external factors are divided into three parts, namely leadership, work climate, and facilities and infrastructure.